Euglenoid pellicle morphogenesis and evolution in light of comparative ultrastructure and trypanosomatid biology: Semi-conservative microtubule/strip duplication, strip shaping and transformation. - Cavalier-Smith, T (Elsevier, 2017)
Uniquely in eukaryotes, euglenoid pellicles comprise longitudinal proteinaceous, epiplasmic strips underlain by microtubules. Contradictory interpretations of pellicle microtubule duplication and segregation assumed opposite microtubule polarity from kinetoplastid Euglenozoa and conservative microtubule segregation. Distigma shows new pellicle microtubules nucleating posteriorly as in trypanosomatids, unifying euglenoid and kinetoplastid pellicle morphogenesis, but strip-growth is unpolarised. Epiplasmic insertion and cutting make new strip junctions between alternating wide and narrow daughter strips that grow intussusceptively. Nanotubules, overlooked epiplasm-associated components, define strip edges. At strip heel/toe junctions all euglenoids have a morphogenetic centre microtubule mt2/3 pair. Arguably, proteolysis, epiplasmic growth, and toe-nanotubule-associated epiplasmic scission initiate daughter strips, separating old mts2/3; new mt2/3/bridge-B assembly, sub-heel scission, nanotubule-bridge-A assembly complete duplication. Only mt2/3 pair fully enters the canal, one master microtubule also the reservoir, other pellicle microtubules terminating near canal rims. A related cytokinesis model involving ciliary attachment zone duplication explains near-universally even spirocute strip number. I consider Serpenomonas and Entosiphon alternating heteromorphic strips developmental stages of 'strip transformation'; explain intergroup diversity of strip morphology and dorsoventral strip differentiation causally by specific pellicle-complex components; propose centrin-based mechanisms for strip shaping and euglenoid movement; unify pellicle cytokinetic microtubule segregation across Euglenozoa; and discuss origin and diversification of pellicle complexes.